The Yo-Yo intermittent recovery test in junior basketball players according to performance level and age group - Vernillo, G.; Silvestri, A.; Torre, A. L. (The Journal of Strength and Conditioning Research, 2012)
The aim of this study was to evaluate the Yo-Yo Intermittent Recovery Test Level 1 (Yo-Yo IR1) ability to discriminate between elite, subelite junior basketball players, and a group of nonathletic healthy male athletes at 3 different age groups (U-14 to U-17). In a cross-sectional design, 119 age-matched participants spread over 3 groups, elite (n = 46), subelite (n = 42) junior basketball players, and nonathletic healthy male athletes (n = 31), were evaluated over a 5-week period. The participants undertook 2 familiarization trials of the Yo-Yo test performance and 3 test sessions on an indoor basketball court. When controlling for the effect of the participants' body mass, the results showed that elite athletes had a significantly higher Yo-Yo performance compared with the subelite athletes (1,271 ± 385 vs. 861 ± 428 m; p < 0.0017; effect size [ES] 1.0 ± 0.35) and the nonathletic group (1,271 ± 385 vs. 738 ± 345 m; p < 0.0017; ES 1.45 ± 0.38). No statistical differences (p > 0.0017; ES from 0.02 to 0.39) were noted between participants' performance levels across age groups. Typical between-performance levels and -age groups differences in the Yo-Yo IR1 were observed. However, when controlling for the effect of the participants' body mass, this study demonstrates that the Yo-Yo test is accurate only to discriminate elite junior basketball players but cannot be used to differentiate the basketball-specific aerobic performance for age.